KAJIAN YURIDIS TAHAPAN PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2024 - SITI HASANAH; Adnan Muksin (Politea : Jurnal Politik Islam, 2023)
The research is entitled "Judicial Study of the Stages of Simultaneous Regional Head Elections in 2024". The research focuses on the stages of the Regional Head Election which will be held simultaneously in 2024 in 37 Provinces for the Governor Election and the Regent/Mayor Election in 514 Regencies/Cities. In the same year there will also be general elections for the President and Vice President, DPR, DPD, Provincial DPRD and Regency/City DPRD in 2024. Based on this description, the problems to be dissected in this research are as follows: (1) Regarding the regulatory system for implementing the stages The 2024 Regional Head Election is based on Law Number 10 of 2016 concerning Regional Head Elections. (2) Judicially reviewing the opportunities and challenges of holding regional head elections in 2024? This legal research is empirical normative research with a conceptual approach, a statutory approach, a sociological approach (socio legal), and a case approach using primary legal materials and secondary legal materials. The research results obtained are that the system for regulating the stages of regional head elections, which consists of preparation and implementation, has been regulated in detail in Law of the Republic of Indonesia Number 1 of 2015 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayor Becomes Law, Law Number 10 of 2016 concerning Second Amendment to Law of the Republic of Indonesia Number 1 of 2015 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning Election of Governors, Regents and Mayors Becomes Law. However, there is still disharmony in several provisions relating to the formation of Ad Hoc Election and Election Boards. The implementation of Regional Head Elections which will be held simultaneously in 2024 has good opportunities from regulations with technical regulations, adequate facilities and infrastructure, sufficient budget from the Provincial, Regency/City APBD and the readiness of election organizers such as the KPU, Bawaslu and DKPP. Meanwhile, existing challenges such as disharmonization of regulations, facilities and infrastructure in disaster-prone areas, budgets in various regions are not sufficient to finance the Regional Head Election and the simultaneous stages of the General Election and Regional Head Election in 2024.